3-dimentional morphometric study of molar furcations (LLC "Endo Press", 2020)
During mechanical debridement of root surface of teeth, it is important to ensure not only the smooth and biocompatible surface, but also make a complete evacuation of removed substrate of periodontal pockets that can be complicated in furcation area. Difficult tool access, complicated instrumentation and lack of complete information about this zone leads to unsatisfactory results of treatment. Therefore, for a full evacuation of microbal biofilm components it is necessary to use manual instruments. Morphometric study of 30 furcations of maxilla teeth allows to form an idea about specificities of this zone. For making correct selection of tools it is necessary to take into consideration the specificity of the treated area, especially furcation.